La Edad de Oro de las Geórgicas, 1.121-154, en la literatura española - Herreros Tabernero, Elena (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
In this paper it is analyzed the pervivence of the Golden Age excursus of the Georgics, book I, in the Spanish Literature and its contamination with other topics as the laus ruris or the praise of Italy.